2021
DOI: 10.1021/acs.jpcc.1c05618
|View full text |Cite
|
Sign up to set email alerts
|

Cyano-Substituted Triptycene-Based Monolayers on Au(111): Tripodal Adsorption, Dipole Engineering, and Charge Transfer

Abstract: Molecules with tripodal anchoring groups are generally capable of forming self-assembled monolayers (SAMs), which, however, frequently suffer from inhomogeneous bonding configurations and limited quality. A suitable platform to avoid these problems are triptycenes, which can be decorated with three substrate-specific anchoring groups and substituted with one or three functional tail groups. Along these lines, selecting thiol and cyano groups as the anchoring and tail functionalities, respectively, we synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 80 publications
1
29
0
Order By: Relevance
“…We think that this statement is also applicable to the acene backbones in general as well as to oligophenylene and oligo­(phenylene ethynylene) backbones, popular in molecular electronics. The only exceptions are probably SAMs with extended aromatic building blocks in the backbone and very high molecular order, for which a considerable lateral band transport, similar to that in organic semiconductors, takes place. , Note that even a lateral linkage of individual aromatic backbones by an aliphatic bridge, as it occurs in the triptycene-based monolayers, does not result in a noticeable increase in τ ET compared to the value for the nonlinked backbones …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We think that this statement is also applicable to the acene backbones in general as well as to oligophenylene and oligo­(phenylene ethynylene) backbones, popular in molecular electronics. The only exceptions are probably SAMs with extended aromatic building blocks in the backbone and very high molecular order, for which a considerable lateral band transport, similar to that in organic semiconductors, takes place. , Note that even a lateral linkage of individual aromatic backbones by an aliphatic bridge, as it occurs in the triptycene-based monolayers, does not result in a noticeable increase in τ ET compared to the value for the nonlinked backbones …”
Section: Resultsmentioning
confidence: 99%
“…21,22 Note that even a lateral linkage of individual aromatic backbones by an aliphatic bridge, as it occurs in the triptycene-based monolayers, does not result in a noticeable increase in τ ET compared to the value for the nonlinked backbones. 66 Note also that even though we do not have strict evidence for an intermolecular mixture in the binary NC-Nap/C6 SAMs, which is essential for the conclusions, general considerations and previous results with binary SAMs do support our assumption. First, the molecular exchange procedure, intentionally chosen for the preparation of the binary SAMs (see section 2 for the technical details), is favorable for intermolecular mixture in contrast to coadsorption, which sometimes results in phase segregation.…”
Section: Thementioning
confidence: 99%
“…Fukushima et al have recently reported the formation of SAMs from tripodal triptycene derivatives such as Trip (Figure a). The molecular tripods, which are structurally rigid and capable of forming uniform monolayers with dense molecular packing by a simple solution process, are expected to serve as a new platform for isolating molecules at solid–liquid interfaces, eliminating the fluctuation and orientation problems of conventional alkanethiol SAMs.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the best orientational order and the smallest molecular inclination are observed for the sample prepared at the elevated temperature and post-annealed at 100 °C. The respective average molecular tilt angle of ∼32.5°is somewhat high as compared to the SAMs of thiolate-anchored triptycenes on Au(111) and Ag(111), 34,36,37 but still reasonable. In view of the moderate roughness of the ITO substrates (see Section 2 for the details), the most likely reason for such a high angle is the possible chemical heterogeneity of the substrate surface (on the atomic scale), resulting in a certain heterogeneity of the bonding configurations as discussed above.…”
Section: Discussionmentioning
confidence: 84%
“…Self-assembled monolayers (SAMs) represent a key element of modern nanotechnology finding application in frontier technology areas such as organic/hybrid solar cells, organic field effect transistors, electrochromic devices, sensors, , molecular electronics, etc. SAMs are generally comprised of rod-like molecules bearing an anchoring group that binds to a specific substrate and a functional tail group constituting the SAM-ambient interface and, along with other parts of the molecules, redefining the physicochemical properties of the substrate. ,, Along with this most frequently used design concept involving a single anchoring group and monodentate bonding to the substrate, molecules with complex or multiple anchoring groups having potentially dipodal, tripodal, or tetrapodal bonding configurations were designed. Such molecules bear the advantage of yielding more robust SAMs with improved electronic coupling to the substrate and flexible control over the density of the tail groups. Among different multidentate configurations, molecular tripods, including in particular triptycene derivatives that can form SAMs on a variety of metal substrates, gain particular attention. The triptycene scaffold consists of three phenyl rings, which are disposed at a dihedral angle of 120° relative to each other.…”
Section: Introductionmentioning
confidence: 99%